2017
DOI: 10.1002/rnc.3794
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized summation‐based triggering mechanism for Lipschitz nonlinear systems

Abstract: Summary In this paper, a decentralized event‐based triggering mechanism for a class of nonlinear control systems is studied. It is assumed that the measurement sensors are geographically distributed and so local event generator modules are employed. Then, a novel periodic triggering condition is proposed for each module, which can potentially reduce the information exchange between subsystems compared with traditional control approaches, while maintaining closed‐loop asymptotic stability. The triggering condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This is demonstrated in our example in Section 5.2. Assumption is the linear growth condition, but there are still many applicable practical systems, eg, an electromagnetic levitation system in our experiment and an inverted pendulum …”
Section: Resultsmentioning
confidence: 99%
“…This is demonstrated in our example in Section 5.2. Assumption is the linear growth condition, but there are still many applicable practical systems, eg, an electromagnetic levitation system in our experiment and an inverted pendulum …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Assumption 1 is more generalized over References 1,3. The following condition is imposed in Reference 7. There exist a function γ(ϵ)0 such that for ϵ>0 truei=1nϵiprefix−1false|δifalse(t,x,ufalse)false|γfalse(ϵfalse)truei=1nϵiprefix−1false|xifalse|,1emi=1,,n. Over the condition (6), Assumption 1 becomes more general by adding the term ϵn|u|. Other conditions of (A3) can represent some models of the inverted pendulum system 13,26 with uncertain mass parameter: x˙1=x2, x˙2={1/(m0+Δm)l2}u+(g/l)sinx1 and so on. However, the control method of References 1,3,7 cannot be applied to this inverted pendulum system due to the nonlinearity of input term {1/(m0+Δm)l2...…”
Section: System Formulation and Problem Statementmentioning
confidence: 99%
“…Other conditions of (A3) can represent some models of the inverted pendulum system 13,26 with uncertain mass parameter: x˙1=x2, x˙2={1/(m0+Δm)l2}u+(g/l)sinx1 and so on. However, the control method of References 1,3,7 cannot be applied to this inverted pendulum system due to the nonlinearity of input term {1/(m0+Δm)l2}u.…”
Section: System Formulation and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The digital controller can estimate the plant's state and the unknown disturbances only based on intermittently measurement outputs, and then, generates the required PI control signals. Second, a new kind of summation‐based triggering condition [30] is proposed, which aims to provide a positive minimum inter‐event time uniformly for a family of controllers parameterised by the verification periods. It is shown that the uniform positive minimum inter‐event time can be guaranteed for the proposed triggering conditions if the signals in the threshold parts can include all of those involved in the dynamics of the corresponding measurement errors.…”
Section: Introductionmentioning
confidence: 99%